Quality of Work Life and Organisational Citizenship Behaviour of Faculty Members in Higher Learning Centres, Kerala- A Position Paper - Dr. Ebby Joseph Idicula, Jyothilakshmi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The magnitude of comfort and complacency that an employee feels from his working organisation is called Quality of Work Life (QWL). The voluntary action carried out by an employee without an expectation of any monetary rewards is pronounced as Organisational Citizenship Behaviour (OCB). The paper aims to propose a few postulations regarding the relationship between QWL and OCB. This is done by considering the teaching staff of higher learning centres as units. The study is purely different from the previous articles mentioning the two terms because this is an attempt to find out the degree of influence of QWL on OCB by considering the other variables such as Organisational Commitment (OC), Job Involvement (JI), Servant Leadership (SL) and Transformational Leadership (TL) in the background of higher learning centres. A conceptual framework is drawn for future empirical validation.